2016
DOI: 10.1186/s12889-016-3888-x
|View full text |Cite
|
Sign up to set email alerts
|

Can CCTV identify people in public transit stations who are at risk of attempting suicide? An analysis of CCTV video recordings of attempters and a comparative investigation

Abstract: BackgroundSuicides incur in all public transit systems which do not completely impede access to tracks. We conducted two studies to determine if we can reliably identify in stations people at risk of suicide in order to intervene in a timely manner. The first study analysed all CCTV recordings of suicide attempters in Montreal underground stations over 2 years to identify behaviours indicating suicide risk. The second study verified the potential of using those behaviours to discriminate attempters from other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 9 publications
0
34
0
1
Order By: Relevance
“… 9 10 Only one publication that focused on Canadian railway locations has used CCTV data to establish possible identifiable behaviour in the moments preceding a suicide. 8 There are no publications which incorporate an analysis of CCTV data of people who have died by rail suicide with first-hand accounts of suicidal behaviour at railway locations, from the perspectives of those who have survived and/or have witnessed such behaviour at railway locations.…”
Section: Introductionmentioning
confidence: 99%
“… 9 10 Only one publication that focused on Canadian railway locations has used CCTV data to establish possible identifiable behaviour in the moments preceding a suicide. 8 There are no publications which incorporate an analysis of CCTV data of people who have died by rail suicide with first-hand accounts of suicidal behaviour at railway locations, from the perspectives of those who have survived and/or have witnessed such behaviour at railway locations.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, over the course of 2 experiments, the authors attempted to identify behaviors indicative of a subsequent suicide attempt at metro stations, and tested how well these behaviors predict an attempt [ 8 ]. In the first experiment, the authors identified key behaviors by having 2-3 observers code both easily observable behaviors (eg, standing near the edge of the platform) and those behaviors requiring interpretation (eg, looking depressed).…”
Section: Resultsmentioning
confidence: 99%
“…Another study [ 9 ] expanded on the findings from the aforementioned study [ 8 ] and used semistructured interviews and questionnaires administered to railway staff in addition to CCTV footage to identify these potential indicator behaviors. The process identified 5 main behaviors: station hopping and platform switching, limited contact with people, allowing trains to pass by, where they stood on the platform, and repetitive behaviors such as walking up and down the length of the platform.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations